ANALISIS MOTIVASI BELAJAR MAHASISWA PENDIDIKAN FISIKA DENGAN MENGGUNAKAN VIRTUAL BASIC OF APLICATION BERBASIS EXCEL - Hajar, Siti; Adeline Silaban; Muhammad Akbar; Paulus G. D Lasmono S (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
This study aims to analyze the learning motivation of Physics Education students of Cenderawasih University Class of 2022 in learning physics, especially in optics material assisted by Excel-based Virtual Lab using 5 indicators of learning motivation, namely: Desire and desire to learn, Drive and need to learn, Interesting activities in learning, enthusiasm in learning, and feelings of pleasure in learning. The method used in this study is a descriptive qualitative method, with the instrument used in the form of a questionnaire containing positive and negative statements aimed at analyzing the learning motivation, especially in optics material. The subjects of the study were all 16 students of Class of 2022. The results of the study, namely by using Excel-based Virtual Basic Of Application, they have very good learning motivation, this is evidenced by the results of the study which shows a percentage of 87.20 and is included in the very good category.. And the implications of this study are that Excel-based VBA allows students to experiment, manipulate variables, and see firsthand the impact of parameter changes in various physics scenarios. This encourages active learning and can support a problem-based learning approach, where students independently find solutions through exploration.